Pengaruh Model Project based Learning (PJBL) dengan Media Scrapbook terhadap Hasil Belajar PPKn (Penelitian Pada Siswa Kelas 3 SD Negeri Podosoko I) - Reza Ervina; Agrissto Bintang Aji Pradana; Putri Meinita (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effect of Project Based Learning Model (PjBL) With Scrapbook Media Toward Learning Outcomes In Civic Education. This research was conducted on three grade students of Primary School Podosoko 1 Magelang regency. This research method is experimental with One Group Pretest-Postest design model. The subjects were chosen by saturated sampling. Samples taken as many 16 student of the experimental group. Method of data completion is done by using test. Test the validity test of instrument by using the formula product moment, and reliability test using cronbach alpha formula by SPSS for windows version 25.00. Data analysis using non parametric statistic technique that is Wilcoxon test by SPSS for windows version 25.00. The results showed that there was a difference in the average value of the experimental class learning outcomes for the pretest 65 and posttest 79. The experimental class with the highest score for the pretest was 81 and posttest was 94. The lowest score for the pretest was 44 and the posttest was 56. The average difference between the pretest and posttest scores was 14. The hypothesized data with Asym sig is 0.001 < 0.05. Therefore it can be concluded that the Project Based Learning Model (PjBL) assisted by the Media Scrapbook affects the learning outcomes of Civic Education for Class 3 Elementary School students in Podosoko 1, Sawangan District, Magelang Regency.